Influence of bi-competitive training on improving the performance capacity of junior female gymnasts - Potop, V.; Cretu, M. (Science, Movement & Health, 2013)
The purpose of this paper is the presentation of bi-competitive training influence on improving the performance capacity of junior female gymnasts. With that end in view, we considered that, by providing an optimum relationship between the means content of bi-competitive training and the requirements of the training category within the same stage of preparation, we shall influence the performance capacity and the successful participation in the scheduled competitions. Methods.The study was organized during five months of training (16 May 2011 - November 5, 2011), applied to a single gymnast, 10 years old, junior IV category, level 2, with the training objective to participate in the National Championships junior IV, level 2, Buzau; "Sergiu Popa" Memorial Gymnastics Competition, Junior III, level 3, Focsani; National Team Championship of Juniors III, level 3, Deva and in Individual National Championship Junior III, level 3, Focsani. Gymnast.s evolutions in the preparatory stages of training sessions and competitions were monitored by using video methods of technical analysis, statistical - mathematical method and graphical representation method. Results. The analysis of means content used in the bi-competitive preparation of female gymnasts junior IV showed that the training sessions aimed at the improvement of technical elements specific to category IV level 2 and at the learning of higher difficulty technical elements required by category III on every apparatus. To highlight the level of performance capacity indices within the bi-competitive training, 5 strength tests were applied, also 3 verification training sessions in each competitive stage and the results obtained on apparatuses in the 4 competitions, as for Score A1 (difficulty value - category requirements ), Score B - execution score and FM - final mean Discussions. The study focused on the physical and technical training programs, monitoring statistically the development of muscle strength and the dynamics of technical elements learning on different apparatuses. Study results show that the bi-competitive training refers to the improvement of performance capacity in women's artistic gymnastics at junior level IV, which during training sessions aimed both at improving the category elements and at learning new and more difficult elements required for participation in competitions of a higher level than gymnast.s age. This training depends entirely on the competitive calendar, on gymnasts. training level and on competitive effort characteristics at different levels of training; this methodological orientation is rare in artistic gymnastics - only with talented children and good working conditions. The analysis of physical training level highlights an improvement of abdominal muscle strength, back and scapular-humeral belt strength, arms and legs strength - spring, all these having a great influence on learning and perfecting the technical elements at apparatus, as required by Junior III category level 3.As for the results of performance capacity indices during the 4 competitions, we noticed an increase of exercises difficulty value on apparatus, an improved execution technique of highly difficult elements and the increase of the final score value on apparatus. Regarding the correlation of performance capacity indices between competitions, we observed insignificant differences of difficulty value at p> 0.05 in terms of requirements of the training category; significant differences of the technical execution score between the first and the second competition at <0.01, while in the contest 3 and 4 the differences are insignificant at p> 0.05 and significant as for the final score between competitions. Conclusions. The training optimization by improving the elements of category IV on each apparatus and the learning of some technical elements necessary for category III in the same training session lead to the bi-competitive training in women.s artistic gymnastics. An optimum relationship provided between the content of means in bicompetitive training and the requirements of the training category within the same stage of preparation will influence the performance capacity and the successful participation in the scheduled competitions. For a correct application of this form of competitive training, its efficient utilization during training sessions is recommended only if we take into account the specific methodological aspects that allow us to use it.